Evaluation Criteria of Safety and Health Induction for Construction Worker (SICW) in Malaysia (Jurnal Teknologi (Sciences & Engineering), 2015)
Workplace safety is one the main concern by facilities managers due to high fatality rates in Malaysia construction industry. Occupational Safety and Health (OSH) training is an important effort to reduce workplace accident and improve employees’ safety and health in construction industry by enhancing the workers’ safety knowledge and awareness on workplace. In Malaysia, Safety and Health Induction for Construction Worker (SICW) or commonly known as Green Card Training, a mandatory safety training, has been introduced by Construction Industry Development Board (CIDB) to the construction related workers in order to enhance the workers’ safety knowledge and awareness on workplace. However, SICW has never been evaluated in term of its effectiveness in delivering safety knowledge and awareness to the workers since it has been introduced. Therefore, an evaluation is needed to be carried out to evaluate the safety knowledge and awareness gain by the workers from SICW. This paper will show the evaluation criteria for SICW based on the topics covered by standardized materials provided by CIDB. The evaluation criteria will serve as a guideline for evaluation of SICW in future research.